2012
DOI: 10.1590/s1413-70542012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of food bars manufactured with agroindustrial by-products and waste

Abstract: Food bars are products obtained from the union of a number of components, standing out in the snack category due to their portability attribute with a focus on convenience and health. Utilization of by-products and agroindustrial food waste as ingredients in the making of food bars is highly important due to the utilization of leftovers of marked nutritional and functional value and decrease of the production cost. This work intended to evaluate the chemical and physicochemical aspects of food bars made with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 9 publications
4
16
0
12
Order By: Relevance
“…Our finding corroborated previous reports that CB are prepared from agroindustrial residues and differed moisture contents in g 100 g −1 , ranging from 9.44 to 11.70 (Paiva et al 2012), 9.73 (Lima et al 2010) and 4.61 (Fonseca et al 2011). This variation is probably due to the components used in the preparation of the bars.…”
Section: Sensory Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding corroborated previous reports that CB are prepared from agroindustrial residues and differed moisture contents in g 100 g −1 , ranging from 9.44 to 11.70 (Paiva et al 2012), 9.73 (Lima et al 2010) and 4.61 (Fonseca et al 2011). This variation is probably due to the components used in the preparation of the bars.…”
Section: Sensory Analysissupporting
confidence: 92%
“…The binder syrup ingredients (brown sugar, glucose syrup and salt), were mixed and heated in a water bath at 90°C for about ten minutes in a stainless steel pot, until reaching soluble solids values from 80°Brix to 85°Brix (Paiva et al 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in minerals are probably due to the type of seeds and ingredients used in the formulation of the oat bars. Similar results were found by Paiva et al [44], who found that cereal bars contain rice, soy and pineapple had higher levels of phosphorus, potassium, magnesium, copper, manganese, zinc and iron. Roy et al [45] mentioned that chickpea is an excellent source of minerals, especially calcium, phosphorous, iron, and magnesium.…”
Section: Chemical Composition Of Oat Barssupporting
confidence: 90%
“…The sodium levels found in CB-2 and CB-5 were statistically equal and lower than that found in CB-1. Paiva et al (2012), studying CBs elaborated with residues of rice, soy, pineapple, and brown pequi, found higher levels of P, K, Mg, Cu, Mn, Zn, and Fe (in mg 100 g -1 ), respectively: 175.0 to 275.0, 242.5 to 495.0, 97.5 to 170.0, 0.53 to 0.91, 1.40 to 1.56, 1.69 to 2.38, and 3.33 to 5.58. These differences are probably due to the type of residue used in the preparation of the CBs.…”
Section: Resultsmentioning
confidence: 99%